Sarmad A. M. AL-Asadi Evaluation Of Fasciola gigantica Excretory-Secretory Antigen on Immunodiagnosis For Cattle Fascioliasis in AL-Chebayish Marshes By Using ELISA - AL-Asadi, Sarmad (University of Thi-Qar Journal of Science, 2019)
Enzyme-Linked Immunosorbent Assay ( ELISA ) was evaluated for ability to detect IgG anti- Fasciola gigantica antibodies in cattle by using F. gigantica excretory-secretory antigen ( FgES ).The presnt study revealed that the sensitivity and specificity were 95% and 100% respectively, when no cross-reactions with sera of cattle infected with other parasites was reported .At the mean time fifty seven random serum samples of cattle were examined by ELISA and revealed that the infection prevalence was 64.9% .